STRATEGIC GUIDELINES FOR THE RECONSTRUCTION OF UKRAINE IN THE CONTEXT OF THE NEW EUROPEAN BAUGAUS: CONTINUITY OF THE DEVELOPMENT OF SCIENCE AND INNOVATION ECOSYSTEMS (INNOVATIVE ECONOMY, 2025)
Voloshchuk Yu.O., Voloshchuk V.R.  STRATEGIC GUIDELINES FOR THE RECONSTRUCTION OF UKRAINE IN THE CONTEXT OF THE NEW EUROPEAN BAUGAUS: CONTINUITY OF THE DEVELOPMENT OF SCIENCE AND INNOVATION ECOSYSTEMSPurpose. The aim of the article is to systematize the content priorities and determine the strategic guidelines for the restoration of Ukraine in the context of the ideas of the New European Bauhaus, as a space for the development of advanced science and innovative ecosystems.Methodology of research. Induction and deduction methods were used to collect, systematize and process information, identify trends and cause-and-effect relationships in the scientific field. Analysis and synthesis methods were used to determine the directions of scientific research in Ukraine and the EU countries. The abstract and logical method was used to summarize information from various sources, form a holistic vision of the research issues, as well as to develop theoretical conclusions and generalizations. A graphical method was used to visually present the research results.Findings. The article reveals the strategic guidelines for the reconstruction of Ukraine in the context of integration into the European space of research and innovation, in particular through the prism of the ideas of the New European Bauhaus. The need to transform traditional approaches to national economic development on the basis of innovation, interdisciplinary and value-based rethinking of space is substantiated.Attention is focused on the creation of innovation ecosystems capable of ensuring a high level of cooperation between universities, business, state structures and society. It is noted that the institutional support of innovation policy should be based on the European principles of openness, accessibility, aesthetics and environmental sustainability. The structure of the Horizon Europe and New European Bauhaus programs is analysed in terms of intercluster cooperation, digital transformation, green economy and strengthening the role of the cultural context in urban development.Key areas in which Ukraine can integrate into a common European research space are identified: the development of regional innovation hubs, support for technology transfer, the formation of architecture of trust between innovation entities, and the stimulation of intersectoral interaction.Originality. Further development of scientific approaches to systematization of content priorities and definition of strategic guidelines for the restoration of Ukraine in the context of the New European Bauhaus as a space for the development of excellent science and innovation ecosystems has been achieved.Practical value. Three strategic scenarios for the development of science and innovation in Ukraine for the period until 2030 were assessed and it was determined that the innovative reconstruction of Ukraine should be based on the ideology of open science, the principles of targeted partnership, taking into account a creative approach to the formation of educational, digital and physical space, which can be used in the formation of strategic plans for the development of scientific projects both at the level of individual scientific institutions, universities, and in the formation of development strategies for regions, enterprises and organizations, innovation clusters when creating innovation ecosystems to stimulate inter-sectoral interaction.Key words: strategic guidelines, New European Bauhaus, science, innovation, intercluster development, innovation hubs, innovation ecosystem.
Keywords: strategic guidelines; New European Bauhaus; science; innovation; intercluster development; innovation hubs; innovation ecosystem